First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

An integrated assessment of fecal sludge management (FSM) in Islamabad, Pakistan: challenges and treatment solutions - N. Maqbool; S. J. Khan; I. Hashmi (International Journal of Environmental Science and Technology, 2025)

Role of water hyacinth (Eichhornia crassipes) in integrated constructed wetlands: a review on its phytoremediation potential - A. Aqdas; I. Hashmi (International Journal of Environmental Science and Technology, 2023)

Central composite rotatable design for optimization of trihalomethane extraction and detection through gas chromatography: a case study - S. Rasheed; I. Hashmi; Q. Zhou; J. K. Kim; L. C. Campos (International Journal of Environmental Science and Technology, 2023)
Central composite rotatable design (CCRD) was employed to optimize initial temperature (ºC), ramp function (ºC/min) and salt addition for trihalomethane extraction/quantification from the drinking water distribution network in Ratta Amral, Rawalpindi., Pakistan. Drinking water samples were collected from the treatment plant, overhead reservoir and consumer’s taps. The USEPA method for trihalomethane detection 551.1 via gas chromatography was applied using liquid–liquid extraction. The experiments with input variables for sample preparation and operational conditions were performed in a randomized order as per design of experiment by central composite rotatable design and responses were evaluated for model development. A significant ( p = 0.005) two-factor interaction model was optimized. Initial temperature was observed to be insignificant ( p = 0.64), while ramp function ( p = 0.0043) and salt addition ( p = 0.04) were significant. Product of salt addition and ramp was significant ( p = 0.004), while product of initial temperature and salt addition was insignificant ( p = 0.008). With a desirability function of 0.97, an initial temperature of 50 ºC, 6 ºC rise/min to 180 ºC and 0.5 g salt were optimized. It was found that development and optimization of the analytical methods for rapid trihalomethane detection would improve optimization of the current treatment practices in the country.

Corrigendum: Influence of Light Availability and Prey Type on the Growth and Photo-Physiological Rates of the Mixotroph Noctiluca scintillans - Helga do Rosario Gomes; Kali McKee; Anxhela Mile; Sharanya Thandapu; Khalid Al-Hashmi; Xiaojian Jiang; Joaquim I. Goes (Frontiers in Marine Science, 2019)

Influence of Light Availability and Prey Type on the Growth and Photo-Physiological Rates of the Mixotroph Noctiluca scintillans - Helga do Rosario Gomes; Kali McKee; Anxhela Mile; Sharanya Thandapu; Khalid Al-Hashmi; Xiaojian Jiang; Joaquim I. Goes (Frontiers in Marine Science, 2018)

High-performing antifouling bacterial consortium for submerged membrane bioreactor treating synthetic wastewater - H. Waheed; S. Pervez; I. Hashmi; S. J. Khan; S.-R. Kim (International Journal of Environmental Science and Technology, 2018)

Mesoscale and Nutrient Conditions Associated with the Massive 2008 Cochlodinium polykrikoides Bloom in the Sea of Oman/Arabian Gulf - Adnan R. Al-Azri; Sergey A. Piontkovski; Khalid A. Al-Hashmi; Joaquim I. Goes; Helga do R. Gomes; Patricia M. Glibert (Estuaries and Coasts, 2014)

Seismic microzonation for Muscat region, Sultanate of Oman - I. El-Hussain; A. Deif; K. Al-Jabri; A. M. E. Mohamed; G. Al-Rawas; M. N. Toksöz; N. Sundararajan; S. El-Hady; S. Al-Hashmi; K. Al-Toubi; M. Al-Saifi; Z. Al-Habsi (Natural Hazards, 2013)

Deterministic seismic hazard assessment for Sultanate of Oman - A. Deif; I. El-Hussain; K. Al-Jabri; N. Toksoz; S. El-Hady; S. Al-Hashmi; K. Al-Toubi; Y. Al-Shijbi; M. Al-Saifi (Arabian Journal of Geosciences, 2013)

Probabilistic seismic hazard maps for the sultanate of Oman - I. El-Hussain; A. Deif; K. Al-Jabri; N. Toksoz; S. El-Hady; S. Al-Hashmi; K. Al-Toubi; Y. Al-Shijbi; M. Al-Saifi; S. Kuleli (Natural Hazards, 2012)

Chlorophyll a as a measure of seasonal coupling between phytoplankton and the monsoon periods in the Gulf of Oman - Adnan R. Al-Azri; Sergey A. Piontkovski; Khalid A. Al-Hashmi; Joaquim I. Goes; Helga R. do Gomes (Aquatic Ecology, 2010)